THE EFFECT OF SUSTAINABILITY REPORTING, FOREIGN OWNERSHIP, LEVERAGE, AND PROFITABILITY ON COMPANY VALUE - Prawita Lestari Ning Katresnan; Zulfikar Zulfikar (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the effect of sustainability reporting (SR), foreign ownership (FO), leverage (LEV), and profitability (ROA) on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. The research employs a quantitative associative approach using secondary data obtained from annual reports and financial statements. Samples were selected purposively based on listing consistency, completeness of financial statements, and availability of relevant variables. Data analysis was conducted using multiple linear regression in SPSS, supported by classical assumption tests and hypothesis testing (F-test, t-test, Adjusted R²). The results indicate that sustainability reporting disclosure has a positive and significant effect on firm value, suggesting that comprehensive SR information enhances company reputation and investor confidence. Profitability (ROA) and leverage (LEV) also have a positive and significant impact, supporting asset efficiency, earnings performance, and the trade-off theory in debt management. In contrast, foreign ownership does not significantly affect firm value, indicating relatively passive involvement of foreign investors. The study is limited by its observation period, focus on the manufacturing sector, and a limited set of variables, so future research is recommended to expand the scope of sectors, periods, and variables.